Analysis of the slackline training impact on human balance- a preliminary report of a randomized trial - Adam Wrzeciono; Oliver Czech; Patryk Szary; Sebastian Rutkowski (Matej Bel University, 2021)
Abstract The development of civilization resulted in the creation of many new sports disciplines. Many of them are still unexplored and the effects and benefits of exercise remain unclear. One of these sports is slacklining, which seems to affect the balance of trainees. The aim of the study was to analyze changes in human balance after a supervised slackline training session. The study enrolled 10 healthy volunteers who were randomly divided into experimental and control groups. Each participant underwent an initial and a final balance assessment using the Tandem Walk protocol on the Balance Master platform. The intervention lasted 5 days, with 15 minutes of supervised training per day. Changes in balance after training were considered as a primary outcome. The analysis of the data showed no significant changes in step width, speed and end sway parameters of Tandem Walk test for both experimental and control group. The results suggest that 5-days, 15-minutes slackline training does not affect the parameters of the task-specific Tandem Walk balance test. DOI: https://doi.org/10.24040/sjss.2020.6.2.16-22